2022
DOI: 10.1002/dta.3225
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bazedoxifene, a selective estrogen receptor modulator, in human urine by liquid chromatography‐tandem mass spectrometry

Abstract: Bazedoxifene, a selective estrogen receptor modulator, has been explicitly included in the prohibited list issued by the World Anti-Doping Agency (WADA) since January 2020. A high-resolution liquid chromatography-tandem mass spectrometric detection method was developed to identify bazedoxifene and its metabolites in human urine and to quantify bazedoxifene (free plus glucuronide) for doping control purposes. Bazedoxifene acetate (20 mg) was orally administered to seven male volunteers, and the urine samples co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Bazedoxifene (Figure 1, 7 ), an SERM, was introduced into WADA's Prohibited List in 2020, and the traceability in routine doping controls was assessed by Okano et al by means of an administration study conducted with seven study participants 76 . Upon oral administration of 20 mg of bazedoxifene acetate, urine was sampled up to 78 h and analyzed by LC–HRMS/MS.…”
Section: β2‐agonists Hormone and Metabolic Modulators And Diureticsmentioning
confidence: 99%
“…Bazedoxifene (Figure 1, 7 ), an SERM, was introduced into WADA's Prohibited List in 2020, and the traceability in routine doping controls was assessed by Okano et al by means of an administration study conducted with seven study participants 76 . Upon oral administration of 20 mg of bazedoxifene acetate, urine was sampled up to 78 h and analyzed by LC–HRMS/MS.…”
Section: β2‐agonists Hormone and Metabolic Modulators And Diureticsmentioning
confidence: 99%
“…The trace level impurities of Impurity-A and Impurity-B present in the Bazedoxifene drug substance or drug product may cause severe harmful effects on human health. The concentration limit of genotoxic impurities, Impurity-A, and Impurity-B was calculated based on TTC [1][2][3][4][5] and maximum daily dose [1][2][3][4][5][6][7][8] . Impurity-A and Impurity-B each must to be controlled at below 75ppm.…”
mentioning
confidence: 99%
“…18 Research into the metabolism of the selective estrogen receptor modulator (SERM) bazedoxifene demonstrated that the most suitable target analyte for routine doping controls would be the glucuronic acid conjugated drug, which was traceable for at least 78 h after a single oral dose of the SERM using LC-MS approaches. 19 In order to improve routine ITPs for the SERMs tamoxifen and toremifene, their common metabolic product referred to as carboxy-toremifene was synthesized and fully characterized, thus being available for future anti-doping test methods. 20 Finally, and particularly relevant for result management and in avoiding unintentional anti-doping rule violations, urinary excretion profiles for rectal corticoid administrations were investigated.…”
mentioning
confidence: 99%